IMPLICATIONS OF APPLYING FAIR VALUE ACCOUNTING TO MODERN FINANCIAL REPORTING - Petrović, Dragana; Radosavac, Adriana; Mashovic, Azemina (Journal of process management and new technologies, 2023)
Abstract: Fair value accounting is a concept whose main goal is to provide quality information about financial status, success and cash flows in order to satisfy the informational needs of investors. By introducing this concept, the focus is placed on the balance sheet and not on the income sheet statement as was in the case of the historical cost concept. The goal of financial reporting is to show assets, liabilities and net assets in the balance sheet at fair value on the balance sheet date. The subject of research in this work is the application of fair value accounting, which will be shown on a concrete example in which equipment will be evaluated according to the concept of historical cost, and then the equipment will be evaluated according to the concept of fair value. After that, a comparison of these two concepts will be made, in order to present the financial effects of valuation on assets and liabilities. The importance of applying historical cost accounting is the correct periodization of income and expenses, while the importance of fair value accounting is the presentation of assets and liabilities according to current market prices. The elaborated moments resulted in the reconciliation and unification of these two concepts, which is realized by the hybrid model of financial reporting.